Prenatal diagnosis of aortopulmonary window – case report and review of the literature - Sylwestrzak, Oskar; Dulko, Justyna; Krekora, Michał; Gulczyńska, Ewa; Kopala, Marek; Respondek-Liberska, Maria (Prenatal Cardiology, 2021)
Aortopulmonary window (APW) is a rare congenital heart malformation, which is characterized by a septal defect between the aorta and the pulmonary trunk. This defect can be isolated or associated with other cardiac anomalies in 25-50% of cases. There is no possibility of spontaneous closure of the defect, so early surgical treatment is essential to prevent complications. APW is a well described malformation in paediatric cardiology and cardiac surgery literature, but it is far less described in publications for obstetricians and perinatologists. The presented patient, after in vitro fertilization, had no abnormal finding in the first trimester observed. Subsequently, cardiomegaly occurred at the 32nd week, and finally the fetus was diagnosed with APW in the tertiary centre for fetal cardiology at the 34th week of gestation. Prenatal diagnosis of this condition sped up the postnatal treatment.